Results of a clinical trial of the efficacy and safety of vildagliptin and metformin fixed combination in real clinical practice in Russia (MASTER study) - N. A. Demidov; M. B. Antsiferov; A. V. Zilov (Сахарный диабет)
BACKGRAUND: The widespread prevalence of type 2 diabetes mellitus (T2DM), high mortality and disability of such patients are the reason for the constant active search for effective approaches to hypoglycemic therapy. Recent years have been marked by a change in the strategy for treatment initiation of T2DM. In clinical studies, evidence has been obtained about the benefits of prescribing combination therapy from the time of diagnosis. It seems important to study this treatment option also in real clinical practice.AIMS: To evaluate the effectiveness and safety of the initiation with Galvus Met® as compared with any other combination therapy approaches used in everyday clinical practice.MATERIALS AND METHODS: multicenter prospective observational study in 15 regions of Russia lasting 6 months. Patients were included in the study after the endocrinologist made a decision on the appointment of therapy. Of the men and women over 18 years of age with first diagnosed or previously untreated type 2 diabetes and a level of glycated hemoglobin >7.5%, two groups were formed. The first group included patients who received vildagliptin + metformin (Galvus Met®) in a fixed dose of 50/1000 mg, n=729, the second — another double combination (with the exception of insulin and GLP-1), n=669. The primary endpoint was defined as the proportion of patients (%) who achieved the level of HbA1c <7.0% without proven hypoglycemia at the end of the observation. The NHPQ questionnaire was used to assess the frequency of hypoglycemia.RESULTS: 1385 patients completed the study. For the other combination therapy group, metformin and sulfonylurea derivatives were most often selected (66.5%). In the Galvus Met® group, 68.7% of patients achieved an HbA1c level of <7.0% without proven hypoglycemia, which is significantly better compared to the group of other combinations (40.7%, p <0.001). Galvus Met® therapy contributed to a significantly greater decrease in HbA1c levels by the end of the study compared to other combinations (delta HbA1c -1.6 ± 0.8% versus -1.4 ± 0.9%, p <0.001). In the same group, the average level of HbA1c reached 6.7 ± 0.6% by the end of the study versus 7.1 ± 0.8% in the comparison group, p <0.001. In the Galvus Met® group, body weight decreased by 3.2 ± 3.9 kg, and in the comparison group by 1.3 ± 4.8 kg, p <0.001. The frequency of hypoglycemia episodes in the Galvus Met® group by the end of the study was significantly lower than in the comparison group: 0.8 ± 0.7 episodes per person, versus 1.4 ± 0.8, p = 0.037. In the Galvus Met® group, there were significantly fewer adverse events (4.9% versus 17.7%, p <0.001).CONCLUSIONS: In real clinical practice, Galvus Met® starting therapy has shown better efficacy and safety in terms of achieving glycemic control, HbA1c dynamics, effects on body weight, the frequency of hypoglycemic conditions compared with other combined oral hypoglycemic therapy.